A sustainable approach for weed and insect management in sweetpotato: breeding for weed and insect tolerant/resistant clones. (3rd February 2023) - Wadl, Phillip A.; Campbell, H. Tyler; Rutter, William B.; Williams, Livy H.; Murphey, Victoria; Culbreath, Julianna; Cutulle, Matthew
Abstract: Weed management is consistently ranked among the top priorities of the United States sweetpotato industry. To provide additional weed and insect management strategies for sweetpotato, we initiated development of insect-resistant germplasm that also has weed tolerance by breeding and selecting for sweetpotato clones that are fast growing and have semi-erect to erect canopy architecture. Field studies were conducted in 2018 and 2019 in Charleston, South Carolina, to quantify the effects of weed-free interval and sweetpotato clone on weed counts for naturally occurring weed species, storage root yield, and insect resistance to the major pests of sweetpotato. Weed-free intervals included plots that were weedy all season and weed-free for 2, 3, and 4 wk after transplanting. Sweetpotato clones evaluated included 'Beauregard', 'Covington', 'Monaco', and six advanced selections with semi-erect to erect plant habit. Significant weed-free interval and sweetpotato clone main effects were observed for all variables measured, but not for their interaction. Two sweetpotato clones, USDA-17-037 and USDA-17-077, were consistent across both years and had the lowest weed counts, exhibited enhanced insect resistance, and were the highest yielding entries. These results demonstrate the potential for development of insect-resistant sweetpotato germplasm with a vigorous, erect plant habit that may be less susceptible to weed interference than cultivars with spreading shoot growth. The combination of germplasm that is both resistant to insect pests and competitive with weeds can provide organic and subsistence sweetpotato growers solutions to these critical issues related to sweetpotato production.